INTEGRATED PERFORMANCE AND IOT-BASED RELIABILITY ASSESSMENT OF OFF-GRID PV SYSTEMS - Joni Eka Candra; Mhd Adi Setiawan Aritonang; Muhammad Nazwan (Sinkron : jurnal dan penelitian teknik informatika, 2026)
Island regions often face unreliable electricity supply due to limited grid infrastructure, resulting in high dependence on diesel generators with significant economic and environmental drawbacks. This study aims to evaluate the performance and reliability of an Internet of Things (IoT)-integrated off-grid solar photovoltaic (PV) system implemented in a small island setting. A 400 Wp off-grid PV system was deployed on Pulau Puteri, Indonesia, and equipped with an IoT-based monitoring platform to enable real-time acquisition of operational data. The methodology includes system design, installation, and continuous monitoring over a 30-day period with 5-minute data intervals. System performance was assessed using Performance Ratio (PR) and Capacity Factor (CF). The system produced 1.6–2.1 kWh/day with PR values of 0.75–0.82 and CF of 16.7%–21.9%, indicating efficient and stable operation under tropical conditions. IoT monitoring enabled continuous data acquisition and early anomaly detection, improving operational reliability. The results confirm that the system meets international performance benchmarks and provides a feasible solution for decentralized energy systems in remote islands. The study contributes an integrated framework combining real-time IoT monitoring and standardized performance evaluation using field data.